Highly-efficient and all-solution-processed red-emitting InP/ZnS-based quantum-dot light-emitting diodes enabled by compositional engineering of electron transport layers. Issue 25 (3rd June 2019) - Chen, Fei; Lv, Peiwen; Li, Xu; Deng, Zhenbo; Teng, Feng; Tang, Aiwei
Abstract : All-solution-processed red-emitting InP/ZnS-based QD-LEDs with a record η EQE of 4.24% are successfully fabricated through the compositional engineering of colloidal ZnO NPs, which act as the electron transport layers. Abstract : We report highly-efficient red-emitting InP/ZnS-based quantum-dot light-emitting diodes (QD-LEDs) fabricated via an all-solution-processed technique, in which colloidal ZnO nanoparticles (NPs) with tailoring compositions act as the electron transport layers (ETLs). The optical band gap, energy level and charge injection capability of ETLs can be manipulated by incorporation of various metal dopants with different valence states and ionic radii into ZnO NPs, and the QD-LEDs with ZnO:Mg NPs as the ETL exhibit a superior device performance over other counterparts. By rational passivation of Cl ions on the surface of ZnO:Mg NPs, a record external quantum efficiency ( η EQE ) of 4.24% is successfully realized in the all-solution-processed red-emitting InP/ZnS-based QD-LEDs. The maximum luminance reaches a record 5595 cd m −2 . The Cl@ZnO:Mg NPs not only provide a well-matched charge balance but also prevent interfacial exciton dissociation, boosting the enhancement of device performance. This work shows an effective composition-modulated interfacial engineering strategy for improving the performance of all-solution-processed QD-LEDs.